Removal Of Cadmium And Chromium Using Titanium Dioxide Nanowires Under Ultraviolet Radiation - Rafindi, Nurrafiq Arina (Universiti Sains Malaysia, 2022)
Divalent cadmium, Cd(II) and hexavalent chromium, Cr(VI) are high toxicity chemical substance which may harmful for human being if the amount uptake is too high through consumption and give great threat to our environment. In this study, it focuses on the ability of TiO2 nanowires to remove Cd(II) and Cr(VI) from aqueous solution. The TiO2 nanowires were synthesized by thermal oxidation with different concentration of KOH catalyst. It involves one step oxidation in this synthesis. The effect of oxidation time and oxidation environment were investigated in the formation of nanowires. The optimum condition in synthesizing vertically array and dense TiO2 nanowires via thermal oxidation was found to be at 750°C for 60 minutes under 2M KOH mist environment. The nanowires formed were long, thin and have full coverage on Ti foil. KOH is very vital for the growth of nanowires as it acts as catalyst for push nanowires to grow longer vertically and inhibit lateral growth. Characterization technique used to investigate and support the formation of TiO2 nanowires include FESEM, HRTEM and XRD. The effectiveness of the synthesized TiO2 nanowires were investigated upon removal of Cd(II) and Cr(VI) to a non-toxic state via photocatalyst reaction under UV light. The concentration measured by taking absorbance value from UV-Vis spectrophotometer as concentration is directly proportional to the absorbance based on Beer-Lambert’s Law. It was found that, nanowires grown under 2M KOH for 60 minutes shows the highest reduction of Cd(II) and Cr(VI) which is 34.52% and 34.57% respectively. The lowest reduction of Cd(II) shown by TiO2 nanowires grown under 1M KOH (1.5%) and TiO2 nanowires formed under 3M KOH have ability to reduce to 17.11% of Cr(VI).